Molecular Epidemiology of Salmonella enterica in Poultry in South Africa Using the Farm-to-Fork Approach - Melissa A. Ramtahal; Anou M. Somboro; Daniel G. Amoako; Akebe L. K. Abia; Keith Perrett; Linda A. Bester; Sabiha Y. Essack (International Journal of Microbiology)
The presence of the zoonotic pathogen Salmonella in the food supply chain poses a serious public health threat. This study describes the prevalence, susceptibility profiles, virulence patterns, and clonality of Salmonella from a poultry flock monitored over six weeks, using the farm-to-fork approach. Salmonella was isolated using selective media and confirmed to the genus and species level by real-time polymerase chain reaction (RT-PCR) of the invA and iroB genes, respectively. Antimicrobial susceptibility profiles were determined using Vitek-2 and the Kirby–Bauer disk diffusion method against a panel of 21 antibiotics recommended by the World Health Organisation Advisory Group on Integrated Surveillance of Antimicrobial Resistance (WHO-AGISAR). Selected virulence genes were identified by conventional PCR, and clonality was determined using enterobacterial repetitive intergenic consensus PCR (ERIC-PCR). Salmonella was present in 32.1% of the samples: on the farm (30.9%), at the abattoir (0.6%), and during house decontamination (0.6%). A total of 210 isolates contained the invA and iroB genes. Litter, faeces, and carcass rinsate isolates were classified as resistant to cefuroxime (45.2%), cefoxitin (1.9%), chloramphenicol (1.9%), nitrofurantoin (0.4%), pefloxacin (11.4%), and azithromycin (11%). Multidrug resistance (MDR) was observed among 3.8% of the isolates. All wastewater and 72.4% of carcass rinsate isolates were fully susceptible. All isolates harboured the misL, orfL, pipD, stn, spiC, hilA, and sopB virulence genes, while pefA, spvA, spvB, and spvC were absent. In addition, fliC was only present among the wastewater isolates. Various ERIC-PCR patterns were observed throughout the continuum with different subtypes, indicating the unrelated spread of Salmonella. This study concluded that poultry and the poultry environment serve as reservoirs for resistant and pathogenic Salmonella. However, there was no evidence of transmission along the farm-to-fork continuum.